High aspect ratio micro-EDM drilling with nano surface finish - Ali , Mohammad Yeakub; Abd. Rahman, Mohamed; Banu, Asfana; Adnan, Shakira; Nadia, Fatin (Springer International Publishing, 2016)
This paper presents the issues related to high aspect ratio in micro drilling on metallic materials using micro electro discharge machining (Micro-EDM). Experimental investigation is carried out by drilling high aspect ratio micro holes on copper workpiece with 1 mm diameter tungsten carbide tool electrode using micro-EDM DT 110 with two varying parameters voltage and capacitance. For the measurement and observation of aspect ratio, roundness, and surface roughness were performed by scanning electron microscope, optical microscope, and WYKO NT1100 optical profiler respectively. The purpose of this paper is to achieve high aspect ratio, accurate roundness, and low surface roughness with the minimum wear of tool electrode within machining time. The data were analyzed by Design Expert software. Emperical models for aspect ratio, roundness, and surface roughness are developed. The analysis revealed that the most influential parameter is capacitance. Multiple optimization of responses showed that the optimum parameter values are 90 V gap voltage and 0.26 μF capacitance which provide 2.4 aspect ratio, 44 μm roundness, and 6.0 μm Ra surface roughness. The desirability achieved by optimization is 73.9%. The models are validated by experiments.